ACTR-66. A PHASE 1, OPEN-LABEL, PERIOPERATIVE STUDY OF IVOSIDENIB (AG-120) AND VORASIDENIB (AG-881) IN RECURRENT IDH1 MUTANT, LOW-GRADE GLIOMA: UPDATED RESULTS. (11th November 2019) - Mellinghoff, Ingo; Cloughesy, Timothy; Wen, Patrick; Taylor, Jennie; Maher, Elizabeth; Arrillaga-Romany, Isabel; Peters, Katherine; Choi, Changho; Ellingson, Benjamin; Lin, Alexander; Thakur, Sunitha; Nicolay, Brandon; et al.
Abstract: BACKGROUND: Ivosidenib (AG-120, IVO) is a first-in-class oral inhibitor of mutant isocitrate dehydrogenase 1 (mIDH1), and vorasidenib (AG-881, VOR) is an oral, potent, brain-penetrant inhibitor of mIDH1/2. Both have been evaluated in glioma patients in ongoing phase 1 studies. In orthotopic glioma models, IVO and VOR reduced 2-hydroxyglutarate (2-HG) levels by 85% and 98%, respectively, despite different brain-to-plasma ratios (< 0.04 vs 1.33). METHODS: Patients with recurrent, nonenhancing, WHO-2016 grade 2/3, mIDH1-R132H oligodendroglioma or astrocytoma undergoing craniotomy were randomized 2:2:1 to IVO 500mg QD, VOR 50mg QD, or no treatment (cohort 1), or 1:1 to IVO 250mg BID or VOR 10mg QD (cohort 2), for 4 weeks preoperatively. Postoperatively, patients continued receiving IVO or VOR (control patients were randomized 1:1 to IVO or VOR). Tumors were assessed for mIDH1 status, cellularity, and 2-HG and drug concentrations. Treated subjects were compared with controls and mIDH1/wild-type banked reference samples. Primary endpoint: tumor 2-HG concentration following IVO or VOR. RESULTS: As of March 1, 2019, 27 patients (18 men; 25/2 grade 2/3) were randomized preoperatively in cohort 1 (IVO 10, VOR 12, untreated 5): 27 received drug (IVO 13, VOR 14); 1 discontinued VOR postoperatively due to disease progression. Of 26 tumors analyzed, 22 were evaluable. Mean brain-to-plasma ratios: 0.13 IVO, 1.59 VOR. Relative to untreated samples, IVO and VOR reduced tumor 2-HG by 92.0% (95% CI 73.2, 97.4) and 92.5% (95% CI 78.1, 97.7), respectively. Common (≥ 4 patients) TEAEs (all cohort 1 patients, all grades): diarrhea (37.0%), constipation, hypocalcemia, and nausea (each 18.5%), anemia, hyperglycemia, pruritus, headache, and fatigue (each 14.8%). Cohort 2 has completed accrual, with analyses ongoing. CONCLUSIONS: In cohort 1 of this phase 1 perioperative study, IVO and VOR demonstrated brain penetrance and lowered 2-HG compared with controls. Updated data from both cohorts will be presented.